The algorithm used for the calculation of gas exchange affects the estimation of O2 uptake kinetics at the onset of moderate-intensity exercise - Francescato, M. P.; Cettolo, V. (Experimental Physiology, 2024)
At the start of a moderate-intensity square-wave exercise, after a short delay, breath-by-breath O2 uptake at the mouth is approximated to a mono-exponential function, whose time constant is considered matched to that of the O2 uptake of the working muscles. We compared the kinetic parameters obtained from the breath-by-breath gas exchange data yielded by the `Independent-breath` algorithm (IND), which accounts for the changes in lung gas stores, with those obtained with the classical `Expiration-only` algorithm (EXP). The two algorithms were applied on the same flow and gas fraction traces acquired on 10 healthy volunteers, performing 10 times the same moderate-intensity exercise transition. Repeated O2 uptake responses were stacked together and the kinetic parameters of a mono-exponential function were estimated by non-linear regression, removing the data pertaining to 1-s progressively longer initial periods (DeltaTr). Independently of DeltaTr, the mean response time (time constant + time delay) obtained for the IND data was faster compared to the EXP data (~43 s vs. ~47 s, P < 0.001), essentially because of shorter time delays. Between DeltaTr = 16 s and DeltaTr = 29s, the time constants of the IND data decreased (30.7 s vs. 28.0 s, P < 0.05; drop = 10%), but less than those of the EXP data (32.2 s vs. 26.2 s, P < 0.001; drop = 23%); with the same DeltaTr, the time constants of the two algorithms` data were not different (P > 0.07). The different decrease in the time constant, together with the different mean response time, suggests that the data yielded by the two algorithms provide a different picture of the phenomena occurring at the beginning of the exercise.